2017
DOI: 10.1111/are.13321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary mannan oligosaccharides in early weaning diets on growth, survival, fatty acid composition and gut morphology of gilthead sea bream (Sparus aurata, L.) larvae

Abstract: Effects of dietary mannan oligosaccharides in earlyweaning diets on growth, survival, fatty acid composition and gut morphology of gilthead sea bream (Sparus aurata, L.) larvae Abstract Early weaning of marine fish larvae with dry diets delays gut maturation and reduces growth rates. In juvenile and adult forms of several marine fish species, inclusion of dietary mannan oligosaccharides (MOS) improves gut integrity and functionality, but the effects of MOS inclusion in gilthead sea bream (Sparus aurata, L.) la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Growth and survival of fingerling fish were improved when fed diets with 0.10%-0.15% MOS inclusion. This was in agreement with other studies that reported the important role of MOS on boosting growth and survival of aquatic species [4,10,[18][19][20]. In contrast, dietary MOS supplementation did not improve growth in sturgeon, Acipenser oxyrinchus desotoi [21] or in common carp, Cyprinus carpio [22].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Growth and survival of fingerling fish were improved when fed diets with 0.10%-0.15% MOS inclusion. This was in agreement with other studies that reported the important role of MOS on boosting growth and survival of aquatic species [4,10,[18][19][20]. In contrast, dietary MOS supplementation did not improve growth in sturgeon, Acipenser oxyrinchus desotoi [21] or in common carp, Cyprinus carpio [22].…”
Section: Discussionsupporting
confidence: 92%
“…Prebiotic inclusion in the diet significantly improved protein utilization in striped catfish, Pangasianodon hypophthalmus [19]. Similar inclusion of MOS in the diet enhances utilization of essential fatty acid in gilthead sea bream, Sparus aurata [10]. Similarly, the feed conversion ratio and protein efficiency ratio were significantly higher in Macrobrachium rosenbergii fed Agrimos [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) and ∑n‐3 PUFA in fish tissues (Eryalçin et al . ) and to reduce levels of triglycerides (TAG) on total membrane neutral lipids (Gallaher et al . ; Torrecillas et al .…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have concluded that the dietary inclusion of MOS can positively influence the health and performance of poultry, swine, and fish (Carbone & Faggio, 2016;Ferket, Parks, & Grimes, 2002;Kogan & Kocher, 2007;Torrecillas, Montero, & Izquierdo, 2014). Several recent reports have demonstrated the effectiveness of MOS in enhancing the health and growth performance of fish, including juvenile striped catfish, Pangasiandon hypophthalmus (Akter, Sutriana, Talpur, & Hashim, 2016) and rainbow trout, Oncorhynchus mykiss (Mínguez, Webster, & Villa, 2016); improving the gut morphology of starry flounder, Platichthys stellatus (Schmidt et al, 2017) and gilthead seabream, Sparus aurata (Eryalçin et al, 2017); and modulating the skin mucous barrier of Atlantic salmon, Salmo salar (Micallef et al, 2017). Although these studies are not directly comparable in terms of dietary regimes, rearing conditions, MOS products, and doses, it is likely that the molecular structure of MOS plays a significant role in the functional effects on the host's intestinal barrier response and physiology (Schiavone et al, 2014).…”
mentioning
confidence: 99%